Классификация полиградиентных магнитных сепараторов - Шведчикова, Ирина Алексеевна; Романченко, Ю. А. (НТУ "ХПИ", 2014)
Проанализированы функциональные и конструктивные особенности существующих разновидностей полиградиентных магнитных сепараторов. На основе анализа информационных источников установлено, что в магнитных сепараторах данного класса нашли преимущественное применение стержневые, пластинчатые, шарообразные и решетчатые полиградиентные (гетерогенные) среды. Построена классификация магнитных сепараторов, учитывающая структурные свойства полиградиентных сред.

The use of poly gradient magnetic separators in various technological processes is considered in the article. Found that magnetic separators are widely used in practice for the extraction of weakly magnetic or fine ferromagnetic inclusions with sizes about 0.05 mm or less from non-magnetic media. Functional and structural features of existing varieties of poly gradient magnetic separators are analyzed. Based on the analysis of information sources identified that in magnetic separators of this class are most commonly used core, lamellar, spherical and lattice poly gradient (heterogeneous) media. Determined that the processes taking place in the working body of the separator - poly gradient media, from theoretical and practical aspects are most important. Classification of magnetic separators in which taking into account the structural properties of poly gradient media determined four major types of magnetically separating devices is presented.
Klassifikacija poligradientnyh magnitnyh separatorov
Keywords: магнитный сепаратор; полиградиентная среда; магнитное поле; сепараторы; переработка исходного сырья; magnetic separator; polygradient media; magnetic field